Typhoid fever in Ethiopia - Getenet Beyene; Daniel Asrat; Yohannes Mengistu; Abrham Aseffa; John Wain (Journal of Infection in Developing Countries)
This review focuses on the reports of salmonellosis by investigators in different parts of Ethiopia, in particular focusing on the levels of typhoid fever. Many of the reports are published in local journals that are not available online. There have been seven studies which diagnosed typhoid fever by laboratory culture and there is no coordinated epidemiological surveillance. All conducted research and reports from different health institutions in Ethiopia indicate that typhoid fever was still a common problem up to the most recent study in 2000 and that the extensive use of first-line drugs has led to the development of multiple drug resistance. In the sites covered by this review, the total number of published cases of typhoid fever dropped over time reflecting the decline in research capacity in the country. Data on the proportion of patients infected by different serovars of Salmonella suggest that the non-Typhi serovars of Salmonella are increasing. The published evidence suggests that typhoid fever is a current public health problem in Ethiopia although population based surveys, based on good microbiological diagnosis, are urgently needed. Only then can the true burden of enteric fever be estimated and the benefit of public health control measures, such as health education, safe water provision, improved food hygienic practices and eventually vaccination, be properly assessed.